Analisis Pengaruh Kinerja Keuangan dan Economic Value Added (Eva) Terhadap Return Saham Pada Perusahaan Sektor Makanan Dan Minuman Yang Terdaftar di Bursa Efek Indonesia - Nur Wahyuni; Nurul saptyani; Syamsuri Rahim (STIM-LPI Makassar, 2023)
The purpose of this study was to determine the effect of Financial Performance and Economic Value Added on Stock Returns in Food and Beverage Sector Companies listed on the Indonesia Stock Exchange for the 2017-2021 period. The research data used is secondary data in the form of Financial Statements of Food and Beverage Sector Companies which registered on the Indonesia Stock Exchange for the period 2017 – 2021. The method of analysis for this research is Descriptive Statistical Analysis, Classical Assumptions Test and Multiple Linear Regression Tests. Based on the results of the analysis obtained, it shows that Financial Performance (Current Ratio) has a positive effect on Stock Returns, and Economic Value Added has a positive effect on Stock Return. The benefits of this research can later be used as a reference as material for consideration in assessing the financial performance of company shares and can also be used as material for consideration in making investment decisions for company investors.